Adsorption Characteristics of Cu2+ on Natural Zeolite from Baiyin, China - Zhao, Baowei; Zhang, Li; D. Narty, Obemah; Li, Ruirui (Asian Journal of Chemistry, 2013)
Heavy metal pollution of soils in Baiyin, China has become a more serious environmental problem. This paper attempts to present adsorption characteristics of Cu2+ on natural zeolite from Baiyin. The results showed that the adsorption depends on lower pH values (pH < 3) is explained by the dissolution of crystal structure and the competitive reaction between copper ions and H+. The results also showed that the reduction in grain size leads to increase in the adsorption capacity of zeolite, in that an increase of zeolite dose results in an increase in the adsorption efficiency. Different electrolytes have different effect on adsorption of Cu2+. The electrolytes employed exhibited the adsorption efficiencies in the order NaNO3 > KNO3 > Mg(NO3)2 > Ca(NO3)2. When the concentration of the electrolyte (NaNO3) is between 0.0001 and 1 mol/L, adsorption capacity decreases initially, which will be attributed with increase in ionic concentration. The adsorption capacity of Cu2+ at 35 ºC was about 9 % more than at 15 ºC. The results also showed that the adsorption capacity increases with an increase in initial concentration of Cu2+. This paper also discusses the kinetics and adsorption isotherms of Cu2+ on zeolite. The pseudo-second order model was found to be appropriate for kinetic analysis of the adsorption of Cu2+, whiles the Langmuir isotherm was well fitted with the experimental data rather than Freundlich isotherm. Experimental data showed that zeolite has the immense potential of immobilizing heavy metals in the study area.